2019
DOI: 10.3390/v12010049
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ligase ITCH Interacts with the Z Matrix Protein of Lassa and Mopeia Viruses and Is Required for the Release of Infectious Particles

Abstract: Lassa virus (LASV) and Mopeia virus (MOPV) are two closely related, rodent-born mammarenaviruses. LASV is the causative agent of Lassa fever, a deadly hemorrhagic fever endemic in West Africa, whereas MOPV is non-pathogenic in humans. The Z matrix protein of arenaviruses is essential to virus assembly and budding by recruiting host factors, a mechanism that remains partially defined. To better characterize the interactions involved, a yeast two-hybrid screen was conducted using the Z proteins from LASV and MOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Filoviruses (e.g., Ebola and Marburg [ 98 ]) and rhabdoviruses (e.g., vesicular stomatitis virus (VSV [ 99 ])) also encode a PPXY motif in their VP40 and M proteins, respectively, that specifically interacts with WW domain containing proteins to facilitate viral release. Arenaviruses also encode a PPXY domain in their matrix Z protein [ 100 ], through which the NEDD4 ligase is recruited [ 101 , 102 ]. However, ubiquitination of the PPXY-containing Z protein of LCMV itself is insufficient for virus budding, suggesting factors other than Z is involved [ 101 ].…”
Section: Viral Factors Involved In Entry To the Escrt Pathwaymentioning
confidence: 99%
“…Filoviruses (e.g., Ebola and Marburg [ 98 ]) and rhabdoviruses (e.g., vesicular stomatitis virus (VSV [ 99 ])) also encode a PPXY motif in their VP40 and M proteins, respectively, that specifically interacts with WW domain containing proteins to facilitate viral release. Arenaviruses also encode a PPXY domain in their matrix Z protein [ 100 ], through which the NEDD4 ligase is recruited [ 101 , 102 ]. However, ubiquitination of the PPXY-containing Z protein of LCMV itself is insufficient for virus budding, suggesting factors other than Z is involved [ 101 ].…”
Section: Viral Factors Involved In Entry To the Escrt Pathwaymentioning
confidence: 99%
“…In the case of NW TCRV and OW MOPV, the YxxL motif does not contribute to the self-budding activity of Z, but it is critical for NP-mediated enhancement of Z-driven VLP budding as well as the incorporation of NP into VLPs [ 97 , 177 , 179 ]. Using a yeast two-hybrid screen, Baillet and colleagues recently uncovered the interaction of two members of the Nedd4 family of HECT E3 ubiquitin ligases, ITCH and WWP1 with Z proteins of MOPV and LASV [ 180 ]. They observed that ITCH was needed for efficient production of infectious virus particles of LCMV, LASV, LUJV and MOPV; and found that direct interaction with this pro-viral host factor was dependent on the PPxY late domain of LASV and MOPV.…”
Section: Evasion Strategies Of the Arenavirus Matrix Protein Zmentioning
confidence: 99%
“…They observed that ITCH was needed for efficient production of infectious virus particles of LCMV, LASV, LUJV and MOPV; and found that direct interaction with this pro-viral host factor was dependent on the PPxY late domain of LASV and MOPV. Thus, this host protein acts as a positive regulator of the late stages of virus infection by enhancing the processes of viral release and virus production [ 180 ]. Independently, a proteomics study conducted by Ziegler and colleagues identified Nedd4 family ubiquitin ligases, including ITCH and WWP1, as partners of the LCMV Z protein, binding specifically to the PPxY motif of LCMV Z.…”
Section: Evasion Strategies Of the Arenavirus Matrix Protein Zmentioning
confidence: 99%
“…The PPxY L-domain motif is known to interact with proteins containing WW-domain(s). L-domain motifs have been identified in single-stranded enveloped RNA viruses (Table 1), including in the Gag proteins of several retroviruses and in the matrix of arenaviruses, rhabdoviruses and filoviruses (Baillet et al, 2019;Bieniasz, 2006;Wirblich et al, 2008). RNA viruses use PPxY L-domain motifs to recruit specific WW-domains of host Nedd4 family members and ultimately the ESCRT complex to facilitate their budding and egress (Bieniasz, 2006).…”
Section: The N-terminal Of S Protein Contains a Ppxy L-domain Motifmentioning
confidence: 99%
“…The term "Late" reflects a late function in the virus life cycle (Garnier et al, 1996;Freed, 2002). L-domain motifs are identified in enveloped RNA viruses such as in the Gag protein of a number of retroviruses and in the matrix of arenaviruses, rhabdoviruses and filoviruses (Baillet et al, 2019;Bieniasz, 2006;Wirblich et al, 2008). The WW-domain is a small domain of 35-40 amino acids, named after two conserved tryptophan (W) residues in the sequence (Bork and Sudol, 1994).…”
Section: Introductionmentioning
confidence: 99%